Formulasi dan Aktivitas Antibakteri Krim Anti Acne Ekstrak Etanol Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) terhadap Staphylococcus epidermidis - Syahrida Dian Ardhany; Sastri Septia; Susi Novaryatiin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Bawang Dayak is one of the typical plants of Borneo which is efficacious as traditional medicine. Empirically Bawang Dayak knows to have properties for skin diseases such as acne. This study aimed to determine the differences in the physical properties of anti-acne cream of Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) bulb ethanol extract on day 0 and day 7 and to determine its antibacterial activity against Staphylococcus epidermidis with Disc Diffusion (Kirby-Bauer) method. The cream formulation was made with various concentrations of Bawang Dayak ethanol extract, F1 (5%), F2 (10%), F3 (15%), and F4 (20%). The results showed that F1 cream on day 0 fulfilled all the requirements for homogeneity, pH, adhesion, and dispersive ability. Furthermore, all anti-acne cream formulations of Bawang Dayak bulb ethanol extract had the ability to inhibit the Staphylococcus epidermidis in F1 (5%), F2 (10%), F3 (15%), and F4 (20%) with inhibition zones were 10.4±0.3 mm; 12.9±3.7 mm; 14.9±0.8 mm; and 14.6±0.5 mm on day 0; and inhibition zones were 12.9±1.5 mm; 16.9±1.0 mm; 19.3±1.0 mm; dan 20.3±1.4 mm on day 7, which means there is an increase in inhibitory power on day 7. This study shows the potential of the ethanol extract of Bawang Dayak bulb as an anti-acne cream, but further research is needed to improve the composition and stability of the formulation so that it can be developed as an anti-acne cream product.